Contribution Of Teacher Performance Commitment And Motivation On Teacher Work Productivity In SMPN Tana Toraja District - Atriani Maria Sappa; Mesta Limbong; Lisa Grasia Kailola (Universitas Ahmad Dahlan, 2023)
This study aims to determine how much dedication and motivation contribute to the job productivity of teachers at SMPN in the Tana Toraja District. This research employed regression analysis and a quantitative methodology. The quantitative technique was chosen for this study since the specifications of this design are methodical, organized, and adequately structured from the beginning to the end of the research design process. This research had 75 participants from 3 UPT SMPNs in Tana Toraja. This study also employed a descriptive method to explain the issue or research findings better. The results of this study indicated that: (1) There Was a significant positive effect between teacher commitment on teacher work productivity in Public Middle Schools in Tana Toraja Regency. This showed that other factors significantly influenced the work productivity of teachers in Public Middle Schools in Tana Toraja Regency. (2) There was a significant favorable influence between teachers' work motivation on teacher work productivity in State Junior High Schools in Tana Toraja Regency. This showed that the higher the teacher's work motivation, the higher the teacher's productivity. (3) There was a significant positive effect between teacher commitment and teacher work motivation on teacher work productivity in Public Middle Schools in Tana Toraja Regency. This showed that the higher the teacher's commitment and work motivation, the higher the teacher's productivity.